PERALIHAN TRANSFORMASI MEDIA PEMBELAJARAN DARI LURING KE DARING DALAM PENDIDIKAN AGAMA ISLAM - Unik Hanifah Salsabila; Antika Melania; Alfia Miftakhul Jannah; Irada Haira Arni; Bunga Fatwa (Al-Muaddib : Jurnal Ilmu-Ilmu Sosial & Keislaman, 2020)
The world of education is feeling a tremendous impact with the Covid-19 pandemic. In the implementation, teaching and learning activities are completely diverted using online media, because it has been recommended by the Government and is expected to help in the learning process, because the learning process of teaching should not stop because of the pandemic. According to the hadeeth of the prophet "Demand Knowledge from buian to liang lahat". Educators are required to ensure that the learning process of teaching runs smoothly or not even if it is only done at home. In the implementation, educators and students can do the learning process using applications connected to the internet network and applications that have been agreed, can use social media applications such as google meet, zoom, whatsApp group, telegram and other supporting applications. With that, educators can monitor students following learning. This is certainly difficult for educators and learners. Especially for educators who are required to be creative in conveying learning materials through online learning media, because it will have an impact on the mental ity of students. In assigning tasks should not incriminate students, not about the final results or targeted grades but how students can easily understand what educators have conveyed. In Islam itself the blessing or useful knowledge is characterized by how everyone is able to practice and understand what educators have conveyed. This covid-19 pandemic can also be an opportunity for the education world, because it can utilize technology as a medium in the learning process But, the problems that exist in this online learning process, not yet fully either students or parents of students can operate online media, the uneven economy of parents of students, so in buying quotas can not be fulfilled.